2018
DOI: 10.4081/gh.2018.622
|View full text |Cite
|
Sign up to set email alerts
|

Geographic access to radiation therapy facilities and disparities of early-stage breast cancer treatment

Abstract: Few studies of breast cancer treatment have focused on the Northern Plains of the United States, an area with a high mastectomy rate. This study examined the association between geographic access to radiation therapy facilities and receipt of breast cancer treatments among early-stage breast cancer patients in South Dakota. Based on 4,209 early-stage breast cancer patients diagnosed between 2001 and 2012 in South Dakota, the study measured geographic proximity to radiation therapy facilities using the shortest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 26 publications
(44 reference statements)
3
34
1
Order By: Relevance
“…Lack of knowledge about cervical cancer as a preventable disease was also reported in our qualitative interviews and focus group discussions as evidenced by misconceptions that cancer is a “ death sentence ” and that it is caused by evil spirits hence could not be prevented or treated. These findings are consistent with those of other studies that have shown that knowledge, availability or lack of it influenced access to healthcare services [2024, 26].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Lack of knowledge about cervical cancer as a preventable disease was also reported in our qualitative interviews and focus group discussions as evidenced by misconceptions that cancer is a “ death sentence ” and that it is caused by evil spirits hence could not be prevented or treated. These findings are consistent with those of other studies that have shown that knowledge, availability or lack of it influenced access to healthcare services [2024, 26].…”
Section: Discussionsupporting
confidence: 93%
“…These findings suggest that health system factors (few treating centres, lack of infrastructure, lack of commodities such as drugs, limited number of radiotherapy machines, frequent breakdowns of radiotherapy machines, high costs of services, few specialists, lack of standardized guidelines, lack of health information system, lack of patient follow-up system and bureaucratic referral system) and social factors (lack of knowledge, fear, stigma, misconceptions, family influences, attitudes, beliefs, influence of traditional and spiritual healers) may play a major role in treatment uptake compared to individual factors. Other researchers found that the cost of medication prescribed for cervical cancer was one of the barriers to adherence [24]. In the USA, young women with no health insurance and low socioeconomic status were likely to delay treatment for breast cancer [20].…”
Section: Discussionmentioning
confidence: 99%
“…Our results strongly suggest that the distance breast cancer patients must travel to access radiation is associated with both their surgical treatment decision (mastectomy vs. BCS) and their decision to receive recommended radiation after BCS. These findings build on previous studies [14][15][16][17][18][19][20][21]23,38,39 and add to a growing body of research that recognizes patient travel distance as an important barrier to access in cancer care, particularly among older and more vulnerable populations. [40][41][42] Our study also helps to illustrate the mechanism through which observed rural-urban survival disparities may occur-patients living farther from treatment facilities are more likely to receive guideline-discordant treatment, and those receiving guideline-discordant treatment experience worse survival outcomes.…”
Section: Discussionsupporting
confidence: 79%
“…Available evidence from mostly state-level studies suggests that patients who live farther from radiation facilities may be more likely to choose mastectomy [14][15][16][17][18][19][20][21][22] or to not complete recommended radiation after BCS. 14,17,[21][22][23] In this study, we evaluate the association between travel distance and choice of surgical treatment (mastectomy vs. BCS) and optimal receipt of radiation after BCS among newly diagnosed breast cancer patients in the Medicare population.…”
Section: Introductionmentioning
confidence: 99%
“…Rurality has been shown to be associated with disparities in breast cancer throughout its spectrum of care [9][10][11][12][13]. Rural women are more likely to receive mastectomy and less likely to receive reconstruction, radiation or chemotherapy [14][15][16][17]. The impact of rurality on breast cancer disparities and speci cally surgical treatment could re ect a number of factors, including travel distance, socioeconomic and educational status, and access to multidisciplinary cancer care [18,19].…”
Section: Introductionmentioning
confidence: 99%